Synthesis and characterization of MCM-41-supported nano zirconia catalysts - Mohamed S. Abdel Salam; Mohamed A. Betiha; Seham A. Shaban; Ahmed M. Elsabagh; Reda M. Abd El-Aal; Fathy Y. El kady (Egyptian Journal of Petroleum)
Series of MCM-41 supported sulfated Zirconia (SZ) catalysts with different loadings (2.5–7.5% wt.) were prepared using direct impregnation method. The acquired solid catalysts were characterized structurally and chemically using X-RD, HRTEM, BET, FT-IR, Raman spectroscopy and TPD analysis. The acidity of the solid catalysts was investigated through cumene cracking and isopropanol dehydration at different temperatures. As the SZ loading increases, the surface acidity of the mesoporous catalysts was enhanced, this was reflected by the higher catalytic activity toward cumene cracking and isopropanol dehydration.